Pembuatan Website Sekolah Menengah Kejuruan Negeri (SMKN) Pringkuku - Mareta Verdina Indrayanti; Sukadi . (Indonesian Journal of Networking and Security (IJNS), 2013)
Abstract : Pringkuku senior high school is vocation which located on Pacitan- Solo street in Ngadirejan village, pringkuku sub district. This school has inaugurated  in 2011 and it don’t has website like other schools. From research and interview result, pringkuku senior high school give information for the society only by  brochure and sosialization. Beside that, the facilities in this school is good and relevan with students necessary, so this school must has a website. It has function to increase the quality of education is better and it can be media to promote and to interest for students that will study at this school, beside that general people can know this school by internet. This website is prospected give information fastly  and accurate for general society and they can be easy to look information about this school  within visit this school, so it makes more effective and efficient. Password : The Making Website in Vocational Senior High School Pringkuku Abstraksi : Sekolah Menengah Kejuruan Negeri (SMKN) Pringkuku merupakan sebuah sekolah kejuruan yang beralamat di Jln. Pacitan-Solo, tepatnya di Ds. Ngadirejan, Kec. Pringkuku. Sekolah tersebut  baru diresmikan tahun 2011. Sekolah tersebut belum mempunyai website, seperti sekolah-sekolah kejuruan yang lain. Dari hasil observasi dan wawancara, SMKN Pringkuku dalam memberikan informasi menggunakan brosur dan sosialisasi. Selain itu sarana dan prasarana di sekolah tersebut juga sudah memadai, sehingga seharusnya sekolah tersebut mempunyai website. Tujuannya yaitu agar mutu pendidikan sekolah tersebut lebih maju dan dapat dijadikan media promosi untuk menarik minat calon siswa, sehingga masyarakat luas lainnya juga dapat mengetahuinya melalui situs internet. Website yang ada diharapkan dapat memberikan informasi secara cepat kepada masyarakat luas, dapat dengan mudah melihat data-data tentang sekolah tanpa berkunjung langsung, sehingga lebih efektif dan efisien. Kata Kunci :    Pembuatan Website Sekolah Menengah Kejuruan Negeri (SMKN) Pringkuku